New bradoriids from the lower Cambrian Mernmerna Formation, South Australia:systematics, biostratigraphy and biogeography - Topper, Timothy P.; Skovsted, Christian B.; Brock, Glenn A.; Paterson, John R. (2007)
An assemblage of bradoriid anthropods from the Mernmerna Formation in the Donkey Bore Syncline, central Flinders Rangers, South Australia contains eleven species, including three species of the enigmatic ornamented spine Mongloitubulus. Four new taxa are described, Onagrocharion tuberosus gen. et sp. nov., Amphikeropsis myklosis gen. et sp. nov., Hipponicharion australis sp. nov. and Mongolitubulus unipinosa sp. nov. The presence of Hipponicharion australis sp. nov. in the upper Mernmerna Formation represents the first occurrence of the genus in Australia and extends the biogeographic range of Hipponicharion to eastern Gondwana. Bradoriid specimens of Mongolitubulus unispinosa sp. nov. exhibiting a single mature ornamented spine attached to the central portion of the carapace provides definitive evidence of a bradoriid affinity or the enigmatic, widespread Mongolitubulus small shelly fossil taxon. The assemblage includes several species that facilitate correlation with the Stansbury basin of South Australia, but also with faunas from other Cambrian palaeocontinents, including Antarctica and Laurentia.